2018
DOI: 10.1002/jhet.3160
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of 1,2,4,5‐Tetrasubstituted and 2,4,5‐Trisubstituted Imidazole Derivatives Involving One‐pot Multicomponent Reaction

Abstract: Sodium lauryl sulfate has been found convenient, versatile, and eco‐friendly catalyst for the synthesis of 1,2,4,5‐tetrasubstituted and 2,4,5‐trisubstituted imidazole derivatives by one‐pot multicomponent reactions at 80°C using water as solvent. This protocol afforded advantages, that is, the metal‐free reaction, purification of products by non‐chromatographic method, and excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 22 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…White solid; mp: 290–295 °C [Lit. 53 266–268 °C]; 1 H NMR (400 MHz, DMSO-d 6 ) δ 12.66 (s, 1H), 7.65–7.62 (m, 2H), 7.52–7.33 (m, 8H), 7.27 (t, J = 7.6 Hz, 2H), 7.18 (t, J = 7.0 Hz, 1H), 6.91 (dd, J = 7.6, 2.1 Hz, 1H), 3.79 (s, 3H) ppm; 13 C NMR (100 MHz, DMSO-d 6 ) δ 160.1, 145.9, 137.6, 135.6, 132.1, 131.6, 130.4, 129.2, 129.0, 128.8, 128.7, 128.4, 127.6, 127.1, 118.1, 114.8, 110.7, 55.7 ppm.…”
Section: Methodsmentioning
confidence: 99%
“…White solid; mp: 290–295 °C [Lit. 53 266–268 °C]; 1 H NMR (400 MHz, DMSO-d 6 ) δ 12.66 (s, 1H), 7.65–7.62 (m, 2H), 7.52–7.33 (m, 8H), 7.27 (t, J = 7.6 Hz, 2H), 7.18 (t, J = 7.0 Hz, 1H), 6.91 (dd, J = 7.6, 2.1 Hz, 1H), 3.79 (s, 3H) ppm; 13 C NMR (100 MHz, DMSO-d 6 ) δ 160.1, 145.9, 137.6, 135.6, 132.1, 131.6, 130.4, 129.2, 129.0, 128.8, 128.7, 128.4, 127.6, 127.1, 118.1, 114.8, 110.7, 55.7 ppm.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we revealed saccharin as a strong corrosive impetus which has fostered another strategy in the field of green methodology which has significant advantages, for example, non-poisonous, eco-accommodating, green, high proficiently, naturally harmless nature, high reactant action, minimal expense [67]. 9) and chiral a-amino acid (10) under mild reaction conditions is developed for the synthesis of novel functionalized polycyclic N-fused pyrrolidine derivatives (11). This synthetic strategy results in the construction of two new CC bonds and one CN bond via a simple catalyst-free one-pot three-component reaction (Scheme-28High items yields are effortlessly acquired by basic filtration of the subsequent hastens and resulting washing with 3-5 mL MeOH (without section chromatography or recrystallization).…”
Section: Scheme23: N-arylpyrrolederivatives Synthesis By Onepottwocom...mentioning
confidence: 99%
“…Additionally, the responses are done in MeOH/H2O which are extensively protected, nontoxic, eco-accommodating, and modest. These novel functionalized pyrrolidine N-melded polycyclic subordinates (11) will furnish an assortment of promising mixtures with underlying variety for additional bioassays and clinical medicines. Further examinations to possible organic exercises and therapeutic objective revelation of mixtures 11 are in progress [68].…”
Section: Scheme23: N-arylpyrrolederivatives Synthesis By Onepottwocom...mentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 Over the years, researchers have introduced wide variety of catalyst for the synthesis of imidazole derivatives. Reports have revealed that zeolite 32 , p-dodecylbenzenesulfonic acid (DBSA) 33 , DABCO 34 44 , Sodium lauryl sulfate 45 , Cu@ imine/Fe 3 O 4 magnetic nanoparticles 46 , sulfamic acid functionalized hollow magnetic spheres 47 have significantly improved the efficiency but environmental aspects remain overlooked. The novelty of this work lies in the fact that we have reported a greener catalyst in the form of brick derived clay which is very economical due to easy availability with simple workup and we have successfully utilized it for the synthesis of benzothiazole/ benzimidazole tethered imidazole derivatives with very good efficiency.…”
Section: Introductionmentioning
confidence: 99%